El apoyo emocional a las familias y su incidencia en la integración social de los niños con autismo - Avilés Mite, Yesenia del Carmen (2018)
The research has the theme of emotional support for families of children with autism in order to enhance the social integration of their children. The author carries out an analysis of the problem at present, corroborating that it is a generalized and worrying topic in all the institutions, in spite of the existence of various materials that constitute guidance guides to parents, identifying as one of the causes the absence of programs planned, well structured, motivating that allow to correctly implement all the existing knowledge and in a practical way. The research is qualitative, responds to a descriptive level. It is based on the Case Study method, and others such as systemic and deductive. The selected sample is 12 people, represented by teachers, students with autism and parents of families………..